Life and the beautiful in Hegel’s system (Revista Eletrônica Estudos Hegelianos, 2023)
The relation between life and the beautiful in Hegel’s system is stated in his most important works and is essential to comprehend both the Hegelian philosophy of nature and of art. It assumes a central role, for example, in Hegel’s problematic partial rehabilitation of physiognomy and phrenology in the interpretation of the Greek statue. Nevertheless, the specific outline of that relation is dispersed through the texts in which Hegel deals with those topics. The article aims at piecing together the logical categories that structure this relation, as well as its concrete signification for the real shapes of art and organism, based on a cross-reading of the texts in which the philosopher treats those objects. From that reading, it is put forward that the adequacy between the concept and apparition, which for Hegel is essential to the beautiful, must be understood as the adequacy between the inner purposiveness of life and the equilibrium of the organism in the healthy human body.